HMI di Era Revolusi Industri 4.0 - Muh. Arwanaz Pasauri (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2022)
This journal discusses the role and strategy of the HMI Organization towards the Indonesian nation and state in facing industrial revolution 4.0, as well as an intellectual benchmark in understanding the readiness of organizations and cadres to guard the changing times. The purpose of this research is to be used as a reference for students as HMI cadres when discussing social change and in facing the challenges of changing times in the era of industrial revolution 4.0.